2020
DOI: 10.3390/app10186192
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Imaging of Cortical Blood Flow by Camera-Based Photoplethysmography at Green Light

Abstract: Intraoperative evaluation of blood perfusion in the brain cortex is an important but hitherto unresolved problem. Our aim was to demonstrate the feasibility of cerebral microcirculation assessment during open brain surgery by using camera-based photoplethysmography (cbPPG) synchronized with an electrocardiograph. Cortical blood flow was monitored in five patients with different diagnoses. Two cases (tumor resection and extra-intracranial bypass grafting) are presented in detail. Blood-flow parameters were visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Recently, an imaging photoplethysmography (iPPG) technique has been proposed for visualization and contactless quantification of tissue blood perfusion 11 , 12 . Unlike traditional ICG-based intraoperative imaging, iPPG does not require any intravenous administration of any substance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, an imaging photoplethysmography (iPPG) technique has been proposed for visualization and contactless quantification of tissue blood perfusion 11 , 12 . Unlike traditional ICG-based intraoperative imaging, iPPG does not require any intravenous administration of any substance.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike traditional ICG-based intraoperative imaging, iPPG does not require any intravenous administration of any substance. Successful application of iPPG at green illumination to assess changes in cortical blood-flow during open brain neurosurgery has been recently demonstrated in our group 11 . However, the use of iPPG in abdominal space is a challenging task due to significant variations of the examined organs morphology caused by respiration and peristalsis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…iPPG obtained from the chest can be used after major surgery to assess the differences in cutaneous perfusion [ 30 ]. It is also used to assess blood perfusion in the brain cortex during open brain surgery [ 196 ]. PulseCam [ 197 ] is a sensitive camera that can capture blood perfusion conveniently and affordably.…”
Section: Potential Applications Of Ppg Signal and Impacts On Healthcarementioning
confidence: 99%
“…However, their particular prototype is a typical PPG-probe that operates in contact with the skin and evaluates the blood-flow parameters at a single point. In contrast, the method of imaging PPG (iPPG) has recently become increasingly used to estimate tissue perfusion in vivo, allowing for the quantification of the spatial distribution of the blood flow parameters [ 28 , 29 ]. Moreover, it was recently shown that iPPG allows for the assessment of the local distribution of arterial vascular tone [ 30 ], as well as vascular resistance [ 31 ].…”
Section: Introductionmentioning
confidence: 99%